2019
DOI: 10.5194/acp-19-3223-2019
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the main primary source profiles of particulate matter across China from 1987 to 2017

Abstract: Abstract. Based on published literature and typical profiles from the Nankai University source library, a total of 3326 chemical profiles of the main primary sources of ambient particulate matter (PM) across China from 1987 to 2017 are investigated and reviewed to trace the evolution of their main components and identify the main influencing factors concerning their evolution. In general, the source chemical profiles are varied with respect to their sources and are influenced by different sampling methods. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(29 citation statements)
references
References 112 publications
(193 reference statements)
3
26
0
Order By: Relevance
“…Si and Ca had relatively high concentrations in this factor. These species were tracer components of fugitive dust ( Bi et al, 2019 ; Lin et al, 2020 ; Manousakas et al, 2017 ; Zhao et al, 2021 ). The second factor was interpreted as secondary nitrate because of high explained variations of NO 3 − and NH 4 + associated with small DISP ranges and were present in relatively high concentrations ( Hasheminassab et al, 2014 ; Tian et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Si and Ca had relatively high concentrations in this factor. These species were tracer components of fugitive dust ( Bi et al, 2019 ; Lin et al, 2020 ; Manousakas et al, 2017 ; Zhao et al, 2021 ). The second factor was interpreted as secondary nitrate because of high explained variations of NO 3 − and NH 4 + associated with small DISP ranges and were present in relatively high concentrations ( Hasheminassab et al, 2014 ; Tian et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the latter, several studies conducted in EU cities have shown that total particle number concentrations can vary as high as a factor of roughly 9 within the same city (Birmili et al, 2013;Buonanno et al, 2011;Mejía et al, 2008;Mishra et al, 2012). Localized spatial variations in urban aerosol PSDs and number concentrations are due in part to the nature of local emission sources near the measurement site and meteorological conditions, including wind speed and direction, temperature, and relative humidity (Baxla et al, 2009;Birmili et al, 2001;Charron and Harrison, 2003;Kaul et al, 2011;Nieto et al, 1994;Rose et al, 2010;Stanier et al, 2004;Swietlicki et al, 2008;Väkevä et al, 2000;Wehner and Wiedensohler, 2003;Weingartner et al, 1997;Yu et al, 2018). Physiochemical processes that can transform an aerosol population over space and time are also very important, such as particle growth due to coagulation and condensation, particle shrinkage due to evaporation, reactive uptake, and wet and dry deposition (Gaston et al, 2014;Limbeck et al, 2003;Lin et al, 2011;Moise and Rudich, 2002;Salma et al, 2011;Tang et al, 2010;Zhu et al, 2002a, b).…”
Section: Considerations For Grouping Urban Aerosol Psd Observations By Geographical Regionmentioning
confidence: 99%
“…A recent study using the GEOS-Chem-TOMAS model identified significant aerosol emissions from biomass burning in India and Indonesia from residential, agricultural, and wildfire sources (Kodros et al, 2018). Direct burning has been reported to be a common technique to eliminate agricultural residuals in both China and India (Bi et al, 2019). The contribution of biomass burning to urban aerosols was confirmed by the high content of water-soluble potassium in the particle phase (Qi et al, 2015;Zheng et al, 2005).…”
Section: Submicron Urban Aerosol Number Psds In Asiamentioning
confidence: 99%
“…The regional pollution of fine particles (PM 2.5 ) has attracted worldwide attention from the public and in the scientific community (Cheng et al, 2016;Li et al, 2017c;Lin et al, 2018;Bi et al, 2019) due to its detrimental effect on visibility and public health (Agarwal et al, 2017;. PM 2.5 pollution in China has been continuously reducing since 2013 as a result of the implementation of the Air Pollution Prevention and Control Action Plan (Zheng et al, 2018;Zhang et al, 2019), especially in the Beijing-Tianjin-Hebei region (BTH) (Li et al, 2017b;Cheng et al, 2019), the Yangtze River Delta (YRD) region, and the Pearl River Delta (PRD) region.…”
Section: Introductionmentioning
confidence: 99%